Nonalcoholic Fatty Liver Disease: A Clinical Approach and Review - Maitreyi Raman; Johane Allard (Canadian Journal of Gastroenterology)
Nonalcoholic fatty liver disease (NAFLD) is the most common cause of incidental elevation of liver enzymes in North America and Europe. Risk factors for NAFLD include body mass index of 25 kg/m2 or greater, central obesity and diabetes mellitus. The spectrum of disease is variable, ranging from simple steatosis with benign prognosis, to non-alcoholic steatohepatitis and cirrhosis, conferring increase in morbidity and mortality. The primary abnormality or ‘first hit’ in patients with NAFLD is insulin resistance leading to hepatic steatosis. The second hit involves multiple proinflammatory cytokines resulting in non-alcoholic steatohepatitis. Treatment is aimed at aggressive risk factor control and weight loss. Currently, there are no pharmacological agents recommended in the treatment of NAFLD, although preliminary studies suggest promising agents in the future.